Clinic, epidemiologic and ecological aspects of disease of lymphogranulematose (ZGM) in rusal areas of the Repablic of Daghestan - A. M. Abuyazidov; D. G. Hachirov; H. E. Kazieva (Юг России: экология, развитие)
It has been revealed, that disease of lymphogranulematose in rural areas is greatly influenced by natural and anthropogenesis elements of ecosystem. Among rist factors in rural areas there are essential, often statistically significal influence of remote biological consequences of intensity of using pesticides and mineral fertilizers.